At Westonci.ca, we make it easy for you to get the answers you need from a community of knowledgeable individuals. Ask your questions and receive detailed answers from professionals with extensive experience in various fields. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform.
Sagot :
Bien, vamos a realizar las operaciones pedidas para cada caso utilizando los valores dados de \( z \) y \( w \). Vamos a calcular tanto el producto \( zw \) como la división \( \frac{z}{w} \).
### (a) \( z = -5 + 4i \), \( w = 2 - 3i \)
Producto \( zw \):
[tex]\[ (-5 + 4i) \cdot (2 - 3i) = (-5) \cdot 2 + (-5) \cdot (-3i) + (4i) \cdot 2 + (4i) \cdot (-3i) \][/tex]
[tex]\[ = -10 + 15i + 8i - 12i^2 = -10 + 23i + 12 \][/tex]
Recordando que \( i^2 = -1 \):
[tex]\[ = 2 + 23i \][/tex]
División \( \frac{z}{w} \):
Para realizar la división de números complejos, multiplicamos numerador y denominador por el conjugado del denominador:
[tex]\[ \frac{-5 + 4i}{2 - 3i} \cdot \frac{2 + 3i}{2 + 3i} = \frac{(-5)(2) + (-5)(3i) + (4i)(2) + (4i)(3i)}{(2)^2 + (3i)^2} \][/tex]
[tex]\[ = \frac{-10 - 15i + 8i + 12}{4 + 9} = \frac{-10 - 7i + 12}{13} \][/tex]
[tex]\[ = \frac{2 - 7i}{13} = -1.6923 - 0.5385i \][/tex]
### (c) \( z = -3 - 2i \), \( w = -5 + i \)
Producto \( zw \):
[tex]\[ (-3 - 2i) \cdot (-5 + i) = (-3)(-5) + (-3)(i) + (-2i)(-5) + (-2i)(i) \][/tex]
[tex]\[ = 15 - 3i + 10i - 2i^2 = 15 + 7i + 2 \][/tex]
Recordando que \( i^2 = -1 \):
[tex]\[ = 17 + 7i \][/tex]
División \( \frac{z}{w} \):
[tex]\[ \frac{-3 - 2i}{-5 + i} \cdot \frac{-5 - i}{-5 - i} = \frac{15 + 3i - 10i - 2i^2}{25 + 1} = \frac{15 - 7i + 2}{26} \][/tex]
[tex]\[ = \frac{17 - 7i}{26} = 0.5 + 0.5i \][/tex]
### (e) \( z = 5 - 2i \), \( w = 6i \)
Producto \( zw \):
[tex]\[ (5 - 2i) \cdot 6i = (5 \cdot 6i) + (-2i \cdot 6i) = 30i - 12i^2 \][/tex]
Recordando que \( i^2 = -1 \):
[tex]\[ = 30i + 12 = 12 + 30i \][/tex]
División \( \frac{z}{w} \):
[tex]\[ \frac{5 - 2i}{6i} = \frac{5 - 2i}{6i} \cdot \frac{-i}{-i} = \frac{(5 \cdot -i - 2i \cdot -i)}{(6i \cdot -i)} = \frac{-5i + 2i^2}{-6} \][/tex]
Recordando que \( i^2 = -1 \):
[tex]\[ = \frac{-5i - 2}{-6} = \frac{2 + 5i}{6} = -0.3333 - 0.8333i \][/tex]
### (g) \( z = -9 + 7i \), \( w = 4 + 9i \)
Producto \( zw \):
[tex]\[ (-9 + 7i) \cdot (4 + 9i) = (-9)(4) + (-9)(9i) + (7i)(4) + (7i)(9i) \][/tex]
[tex]\[ = -36 - 81i + 28i + 63i^2 = -36 - 53i + 63 \][/tex]
Recordando que \( i^2 = -1 \):
[tex]\[ = -99 - 53i \][/tex]
División \( \frac{z}{w} \):
[tex]\[ \frac{-9 + 7i}{4 + 9i} \cdot \frac{4 - 9i}{4 - 9i} = \frac{(-9)(4) + (-9)(-9i) + (7i)(4) + (7i)(-9i)}{(4)^2 + (9i)^2} = \frac{-36 + 81i + 28i - 63i^2}{16 + 81} \][/tex]
Recordando que \( i^2 = -1 \):
[tex]\[ = \frac{-36 + 109i + 63}{97} = \frac{27 + 109i}{97} = 0.2784 + 1.1237i \][/tex]
Resumimos los resultados para cada caso:
(a) \( zw = 2 + 23i \), \(\frac{z}{w} = -1.6923 - 0.5385i \)
(c) \( zw = 17 + 7i \), \(\frac{z}{w} = 0.5 + 0.5i \)
(e) \( zw = 12 + 30i \), \(\frac{z}{w} = -0.3333 - 0.8333i \)
(g) [tex]\( zw = -99 - 53i \)[/tex], [tex]\(\frac{z}{w} = 0.2784 + 1.1237i \)[/tex]
### (a) \( z = -5 + 4i \), \( w = 2 - 3i \)
Producto \( zw \):
[tex]\[ (-5 + 4i) \cdot (2 - 3i) = (-5) \cdot 2 + (-5) \cdot (-3i) + (4i) \cdot 2 + (4i) \cdot (-3i) \][/tex]
[tex]\[ = -10 + 15i + 8i - 12i^2 = -10 + 23i + 12 \][/tex]
Recordando que \( i^2 = -1 \):
[tex]\[ = 2 + 23i \][/tex]
División \( \frac{z}{w} \):
Para realizar la división de números complejos, multiplicamos numerador y denominador por el conjugado del denominador:
[tex]\[ \frac{-5 + 4i}{2 - 3i} \cdot \frac{2 + 3i}{2 + 3i} = \frac{(-5)(2) + (-5)(3i) + (4i)(2) + (4i)(3i)}{(2)^2 + (3i)^2} \][/tex]
[tex]\[ = \frac{-10 - 15i + 8i + 12}{4 + 9} = \frac{-10 - 7i + 12}{13} \][/tex]
[tex]\[ = \frac{2 - 7i}{13} = -1.6923 - 0.5385i \][/tex]
### (c) \( z = -3 - 2i \), \( w = -5 + i \)
Producto \( zw \):
[tex]\[ (-3 - 2i) \cdot (-5 + i) = (-3)(-5) + (-3)(i) + (-2i)(-5) + (-2i)(i) \][/tex]
[tex]\[ = 15 - 3i + 10i - 2i^2 = 15 + 7i + 2 \][/tex]
Recordando que \( i^2 = -1 \):
[tex]\[ = 17 + 7i \][/tex]
División \( \frac{z}{w} \):
[tex]\[ \frac{-3 - 2i}{-5 + i} \cdot \frac{-5 - i}{-5 - i} = \frac{15 + 3i - 10i - 2i^2}{25 + 1} = \frac{15 - 7i + 2}{26} \][/tex]
[tex]\[ = \frac{17 - 7i}{26} = 0.5 + 0.5i \][/tex]
### (e) \( z = 5 - 2i \), \( w = 6i \)
Producto \( zw \):
[tex]\[ (5 - 2i) \cdot 6i = (5 \cdot 6i) + (-2i \cdot 6i) = 30i - 12i^2 \][/tex]
Recordando que \( i^2 = -1 \):
[tex]\[ = 30i + 12 = 12 + 30i \][/tex]
División \( \frac{z}{w} \):
[tex]\[ \frac{5 - 2i}{6i} = \frac{5 - 2i}{6i} \cdot \frac{-i}{-i} = \frac{(5 \cdot -i - 2i \cdot -i)}{(6i \cdot -i)} = \frac{-5i + 2i^2}{-6} \][/tex]
Recordando que \( i^2 = -1 \):
[tex]\[ = \frac{-5i - 2}{-6} = \frac{2 + 5i}{6} = -0.3333 - 0.8333i \][/tex]
### (g) \( z = -9 + 7i \), \( w = 4 + 9i \)
Producto \( zw \):
[tex]\[ (-9 + 7i) \cdot (4 + 9i) = (-9)(4) + (-9)(9i) + (7i)(4) + (7i)(9i) \][/tex]
[tex]\[ = -36 - 81i + 28i + 63i^2 = -36 - 53i + 63 \][/tex]
Recordando que \( i^2 = -1 \):
[tex]\[ = -99 - 53i \][/tex]
División \( \frac{z}{w} \):
[tex]\[ \frac{-9 + 7i}{4 + 9i} \cdot \frac{4 - 9i}{4 - 9i} = \frac{(-9)(4) + (-9)(-9i) + (7i)(4) + (7i)(-9i)}{(4)^2 + (9i)^2} = \frac{-36 + 81i + 28i - 63i^2}{16 + 81} \][/tex]
Recordando que \( i^2 = -1 \):
[tex]\[ = \frac{-36 + 109i + 63}{97} = \frac{27 + 109i}{97} = 0.2784 + 1.1237i \][/tex]
Resumimos los resultados para cada caso:
(a) \( zw = 2 + 23i \), \(\frac{z}{w} = -1.6923 - 0.5385i \)
(c) \( zw = 17 + 7i \), \(\frac{z}{w} = 0.5 + 0.5i \)
(e) \( zw = 12 + 30i \), \(\frac{z}{w} = -0.3333 - 0.8333i \)
(g) [tex]\( zw = -99 - 53i \)[/tex], [tex]\(\frac{z}{w} = 0.2784 + 1.1237i \)[/tex]
We hope this was helpful. Please come back whenever you need more information or answers to your queries. Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. Keep exploring Westonci.ca for more insightful answers to your questions. We're here to help.